Teori Kesetaraan Melalui Eksplorasi Kesakralan Teks - Deddy Ilyas (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
Equality, has become a problem even a long time ago-and continues in the future. Equality even became an important discus- sion agreed by the participating countries on the UN commission council for women in March 2004 ago. Put simply, the principles of equality arise because of the inequalities of male masculinity that are beginning to be threatened by the changes that have occurred in women’s recent existence. These changes encourage men to break out of the rigid divide of gender roles, both in the domestic and public spheres. The Qur’an, which is seen by most Muslims as the word of Allah, when it is understood in a mere textual way, will produce a hi- erarchical tendency of understanding that is sacral and bias a barrier to the implementation of equality. This paper is a small reconcilia- tion attempt of contemporarly contemplated views of equality which should be the idea of conservative masculinity associated with Islam.